Implementasi Akomodasi Yang Layak Bagi Penyandang Disabilitas Dalam Proses Penyidikan Di Kepolisian Kabupaten Sleman - Devi, Rosa Pijar Cahya; Prasetio, Ignatius Loyola Iswaradatta (UI Scholars Hub, 2022)
Indonesia is a country that upholds human rights. The manifestation of Indonesia's commitment to supporting human rights is to provide equal opportunities for every citizen to access justice. To provide fair treatment so that every citizen can access justice, Indonesia provides affirmative discrimination to vulnerable groups through laws and regulations. One of affirmative discrimination is provided to groups with disabilities. Through Government Regulation No. 39 of 2020 on Procedural Accommodation for Persons with Disabilities in the Judicial Process, Indonesia regulates what rights must be given to persons with disabilities to be able to participate in any judicial process based on equal rights, including the investigation process. This research aims to determine whether the regulation of the rights of persons with disabilities in the judicial process is already well implemented in the police investigation process. The normative-empirical juridical research method was used by reviewing library data and conducting direct interviews with the parties involved in the field. As a result, the implementation of procedural accommodation for persons with disabilities in the investigation process is still minimal and needs to be improved. The Indonesian government needs to budget more funds to provide procedural accommodation for persons with disabilities so that they can participate in the investigation process properly and effectively